ANALISIS SEKTOR UNGGULAN DALAM MENINGKATKAN PEREKONOMIAN DAN PEMBANGUNAN WILAYAH KABUPATEN KUANTAN SINGINGI - Novrilasari, Dylla; Falatehan, A. Faroby (Jurnal Manajemen Pembangunan Daerah, 2009)
Kuantan Singingi is one of the regencies in Riau Province. Formerly, It was a sub district of Indragiri Hulu regency. Kuantan Singingi regency doesn’t have income from oil and gas sector, however it has great potential natural resources. One of the development policies to advance Kuantan Singingi is to give attention for developing leading sectors which is hoped can be rising up or be locomotif of economic regional. The result of research showed that leading sectors in Kuantan Singingi regency are agriculture, mining and quarrying. The results of skalogram analysis found that Kuantan Tengah district take the firt level on development facilities availability and promoting leading sectors. The lowerest level went to Hulu Kuantan district.Local Government of Kuantan Singingi regency is hoped to be able to support its society economic activities by making priority on agriculture sector, mining and quarrying sector. This priority is important, because LQ analysis found that both sectors are the basis of economy sectors which can increase both the economy and regional development as well as can support non basis of the economy development sectors.Keywod: leading sectors, the economy, development regional